2010
DOI: 10.1590/s1677-04202010000400007
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide induced alleviation of toxic effects of short term and long term Cd stress on growth, oxidative metabolism and Cd accumulation in Chickpea

Abstract: The present study investigates the effect of long and short term Cd stress in chickpea plants and evaluates the protective effect of exogenous nitric oxide (NO) supplementation using sodium nitroprusside (SNP). Cadmium treatments were given before sowing (long term stress) and thirty days after germination (short term stress). Sodium nitroprusside was given as foliar spray 30 days after germination to both long and short term Cd treated plants. Cadmium adversely affected the membranes as was evident from incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 52 publications
4
16
0
Order By: Relevance
“…Similar to our results, Bharwana et al (2014) reported that Pb addition caused a significant increase in Pb concentration in all three observed plant parts of cotton, with the roots having significantly higher levels than the stems and leaves. On the other hand, Kumari et al (2010) also found that different parts of chickpea plants exhibited augmented cadmium content after both short and long term Cd exposures. An increase by 17, 52, 15, 6, 11 and 24-folds in Cd content comparing to control plants was found in root, nodules, stem, leaves, pod covering and seed, respectively, under long term Cd stress while these the short term stress resulted in a lesser accumulation of Cd in different plant parts.…”
Section: Assay Of Lead Content In Different Plant Partsmentioning
confidence: 88%
See 2 more Smart Citations
“…Similar to our results, Bharwana et al (2014) reported that Pb addition caused a significant increase in Pb concentration in all three observed plant parts of cotton, with the roots having significantly higher levels than the stems and leaves. On the other hand, Kumari et al (2010) also found that different parts of chickpea plants exhibited augmented cadmium content after both short and long term Cd exposures. An increase by 17, 52, 15, 6, 11 and 24-folds in Cd content comparing to control plants was found in root, nodules, stem, leaves, pod covering and seed, respectively, under long term Cd stress while these the short term stress resulted in a lesser accumulation of Cd in different plant parts.…”
Section: Assay Of Lead Content In Different Plant Partsmentioning
confidence: 88%
“…Reducing crop yield under Pb stress has been reported by other researchers (Balba et al 1991;Chatterjee et al 2004;Hussain et al 2006). Similarly, Jhanji et al (2012) and Kumari et al (2010) found that in chickpea and Brassica napus Cd toxicity adversely affected seed yield but exogenous NO improved this trait.…”
Section: Stomatal Conductancementioning
confidence: 90%
See 1 more Smart Citation
“…They also observed that NO‐mediated Cd tolerance involves enhanced uptake of indole 3‐acetic acid (IAA) by inhibiting the activity of IAA oxidase. Application of SNP in the form of foliar spray improved long‐ and short‐term Cd tolerance in chickpea plants by significantly decreasing ion leakage and lipid peroxidation levels, while increasing the activities of antioxidant enzymes and redox ratios (Kumari et al ). Recent studies have also reported the ameliorative role of H 2 S and NO to Al‐mediated toxicity and reversal of toxic effects on plant physiology and yield (He and Li ).…”
Section: Functional Cross‐talk Of H2s and No Systems Under Multiple Amentioning
confidence: 99%
“…Mostofa et al (2015) Brassica napus Alleviates the toxic effects of Cd and improves plant growth, enhances the photosynthetic parameters, enhances the antioxidant activities and maintains cellular structures in the leaves and rootsAli et al (2014a) Medicago sativa Decreases lipid peroxidation and differentially modulates the activities and transcripts of antioxidant enzymes, including SOD, APX and PODLi et al (2012) Solanum nigrum NO Increases lateral roots and adventitious rootsXu et al (2011) Cicer arietinum Decreases ion leakage and lipid peroxidation levels, increases the activities of antioxidant enzymes and the redox ratios; exhibits positive effect on seed yield and Cd accumulationKumari et al (2010) Medicago truncatula Improves root growth and reduces ROS accumulation in roots; reduces auxin degradation by inhibiting the activity of IAA oxidase; enhances the uptake of K + decrease GSH and ascorbate (ASC) content; increase the specific activities of antioxidant enzymes. Prevents accumulation of NH 4 decrease the activity of glutamine synthetase, and increase the specific activity of phenylalanine ammonia lyaseHsu and Kao (2004) Helianthus annuus Significantly reversed the loss in dry weight and chlorophyll decay induced by the metal; decreases lipid peroxidation and ASC content and increase in GSH content; decreases SOD activity and increases CAT activityLaspina et al induced MDA accumulation, increases chlorophyll content, net photosynthetic rate and maximal photochemical efficiency (Fv/Fm); significant elevation of depressed CAT activities; improves root POD activity; reduces Al uptake, but elevated concentrations of S, P, Ca, Mg and Fe in plants Dawood et al (2012) Triticum aestivum Increases the activities of amylases and esterases, and maintains lower levels of MDA and H 2 O 2 in germinating seeds of wheat; increases the activities of guaiacol peroxidase, APX, SOD and CAT, and decreases the activities of LOX.…”
mentioning
confidence: 99%